2011
DOI: 10.1262/jrd.10-073k
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern of Progranulin in the Human Placenta and Its Effect on Cell Proliferation in the Choriocarcinoma Cell Line BeWo

Abstract: Abstract. Expression of the glycoprotein progranulin has been recently identified in rodent trophoblast cells during early embryonic development. The aim of our study was to describe the expression pattern of progranulin in human placental tissue specimens by immunostaining. We further analyzed the influence of progranulin on invasion and migration of isolated first trimester villous trophoblast cells. The effect of progranulin on cell proliferation was investigated using the human choriocarcinoma derived cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…It might be expected therefore that the development in grn −/− mice would be severely disrupted. This turns out not to be the case, with grn −/− mice developing normally to term, maturing, and being fertile as adults (Stubert et al 2011;Yin et al 2010a), although reduced germline transmission was reported (Ahmed et al 2010;Wang et al 2010). As discussed above, grn −/− mice show abnormal peripheral inflammatory responses, and a correspondingly excessive activation of microglia was observed in the CNS of grn −/− mice upon inflammatory stimulation (Yin et al 2010a).…”
Section: In Vivo and In Vitro Models Of Pgrn Actionmentioning
confidence: 98%
See 1 more Smart Citation
“…It might be expected therefore that the development in grn −/− mice would be severely disrupted. This turns out not to be the case, with grn −/− mice developing normally to term, maturing, and being fertile as adults (Stubert et al 2011;Yin et al 2010a), although reduced germline transmission was reported (Ahmed et al 2010;Wang et al 2010). As discussed above, grn −/− mice show abnormal peripheral inflammatory responses, and a correspondingly excessive activation of microglia was observed in the CNS of grn −/− mice upon inflammatory stimulation (Yin et al 2010a).…”
Section: In Vivo and In Vitro Models Of Pgrn Actionmentioning
confidence: 98%
“…PGRN, which occurs in the trophoblasts of the preimplantation embryo (Diaz-Cueto et al 2000;Qin et al 2005), stimulates blastocyst formation and implantation (Diaz-Cueto et al 2000;Qin et al 2005) as well as the subsequent formation of the placenta (Desmarais et al 2008;Stubert et al 2011). It might be expected therefore that the development in grn −/− mice would be severely disrupted.…”
Section: In Vivo and In Vitro Models Of Pgrn Actionmentioning
confidence: 99%
“…[51][52][53][54][55][56] Their tight chronological profile in individual women over the course of pregnancy and their synthesis in placental tissue provide a strong rationale for further examining their utility as biomarkers. 57,58 GPC3 is a member of the cell surface heparan sulfate proteoglycan family and regulates cell growth by facilitating Wnt and suppressing Hedgehog signaling. [59][60][61] GPC3 is also cleaved from the cell surface and then acts as a competitive inhibitor of Wnt.…”
Section: Figurementioning
confidence: 99%
“…[64][65][66][67][68][69][70] GRNs are cleaved from progranulin, a secreted glycoprotein that is widely expressed in epithelia, immune cells, the central nervous system, and solid organs including the placenta. 58,71 Loss-of-function mutations have been associated with a dysregulated and proinflammatory immune responses. 72 Two recent studies reported increased placental expression of GRNs in women with preeclampsia and IUGR and increased serum GRNs in women with late-onset preeclampsia.…”
Section: Figurementioning
confidence: 99%
“…Taking the high expression of PGRN by the human placental tissue into account, as well as its inhibitory effect on insulin signaling, it can be hypothesized that PGRN could play a role in the development of insulin resistance during pregnancy (10,11). No study so far has addressed the role of circulating PGRN in pregnancy or GDM.…”
Section: Introductionmentioning
confidence: 99%